Functional bakery products - an overview and future perspectives - Pinto, D. (2014)
Consumers demand for healthier food products that prevent nutrition-related diseases and improve physical and mental well-being have led to the accelerated growth of the functional foods market. Nowadays, the bakery industry seeks to improve the health attributes of their products through using functional ingredients that in some way can lead to healthier food products. There are five main markets for functional foods, namely beverages, dairy products, confectionery products, bakery products, and breakfast cereals. The major areas of development for functional foods are related to gastrointestinal health and immunity, prevention of cardiovascular diseases and cancer, weight control, insulin sensitivity and control of diabetes, and mental and physical performance.